BAX326 (RIXUBIS): a novel recombinant factor IX for the control and prevention of bleeding episodes in adults and children with hemophilia B (2014)
Abstract: Hemophilia B management has improved considerably since the introduction of high-purity plasma-derived factor IX (pdFIX) products in the early 1990s. Recombinant FIX (rFIX) was introduced more recently and has potential safety advantages over the older bloodbased products. Until recently, only one such product, nonacog alfa (BeneFIX®, Pfizer, Inc.), has been available. However, a new rFIX product, BAX326 (RIXUBIS, Baxter Healthcare Corp.), has now been approved by the US Food and Drug Administration. BAX326 undergoes rigorous virus elimination and purification steps during manufacture, and has low activated FIX activity, which confers low thrombogenic potential in humans. Preclinical studies showed promising pharmacokinetic and safety profiles, and these early findings have since been expanded in a series of prospective, multicenter, clinical studies. Foremost among these is a pivotal phase I/ III study of BAX326 and its use in routine prophylaxis or on-demand treatment in patients aged 12–65 years with severe (FIX level <1%) or moderately severe (FIX level ⩽2%) hemophilia B. This study confirmed the pharmacokinetic equivalence of BAX326 and nonacog alfa, and showed a significant reduction in annualized bleeding rate with BAX326 prophylaxis compared with on-demand treatment (79% versus historic controls; p<0.001). The hemostatic efficacy of BAX326 was rated as ‘excellent’ or ‘good’ in 96% of bleeds. BAX326 was also associated with statistically significant and clinically meaningful improvements in physical health-related quality of life. Results are similarly encouraging in a pediatric study in children aged up to 12 years and in a study in hemophilia B patients undergoing surgery. A further study showed safe transition, with no inhibitor formation in any patient, from treatment with a pdFIX product to BAX326. Overall, the safety profile of BAX326 in clinical trials has been strong, with no inhibitor or specific antibody formation, thrombosis, or treatment-related serious adverse events or anaphylaxis.